2001
DOI: 10.1093/jexbot/52.357.877
|View full text |Cite
|
Sign up to set email alerts
|

A novel Coptis japonica multidrug‐resistant protein preferentially expressed in the alkaloid‐accumulating rhizome1

Abstract: A full-length cDNA, Cjmdr1, which belongs to the multidrug-resistant (mdr) gene family, was isolated by nested RT-PCR from alkaloid-producing cultured cells of Coptis japonica. The cDNA is 4192 nucleotides long and has an ORF of 1289 amino acids. Northern analysis of the intact plant showed a clear preference in its expression in the rhizome, where alkaloids are highly accumulated compared to other organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…In tobacco, the plasma membrane-localized NUP1 moved apoplastic nicotine into the cytoplasm. Similarly, the C. japonica CjMDR1 mobilizes the alkaloid berberine from the apoplast into the cytoplasm (28,41). However, NUP1 and CjMDR1 differ in how the alkaloid uptake is energized.…”
Section: Discussionmentioning
confidence: 99%
“…In tobacco, the plasma membrane-localized NUP1 moved apoplastic nicotine into the cytoplasm. Similarly, the C. japonica CjMDR1 mobilizes the alkaloid berberine from the apoplast into the cytoplasm (28,41). However, NUP1 and CjMDR1 differ in how the alkaloid uptake is energized.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial separation of product formation and storage implicates the intercellular transport of protoberberine alkaloids from the protoderm to cortical and pith cells. A molecular clone for a multidrug-resistance protein (MDR)-type ATP binding cassette (ABC) transporter (Cjmdr1), identified as a putative berberine transporter, has been isolated (Yazaki et al, 2001) and characterized (Shitan et al, 2003) from C. japonica. RNA gel blot and in situ hybridization analyses showed the abundant and preferential expression of Cjmdr1 in the rhizome (Yazaki et al, 2001) and suggested the localization of gene transcripts to xylem tissues (Shitan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A molecular clone for a multidrug-resistance protein (MDR)-type ATP binding cassette (ABC) transporter (Cjmdr1), identified as a putative berberine transporter, has been isolated (Yazaki et al, 2001) and characterized (Shitan et al, 2003) from C. japonica. RNA gel blot and in situ hybridization analyses showed the abundant and preferential expression of Cjmdr1 in the rhizome (Yazaki et al, 2001) and suggested the localization of gene transcripts to xylem tissues (Shitan et al, 2003). In C. japonica, berberine accumulates mainly in the rhizome, whereas alkaloid biosynthetic enzymes have been associated with roots (Fujiwara et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified a PM PGP transporter, MDR1, in the model isoquinoline alkaloid producer, Coptis japonica, and demonstrated that the protein mediated ATP-dependent berberine uptake (Yazaki et al, 2001;Sakai et al, 2002;Shitan et al, 2003;Yazaki, 2005). A survey of the Arabidopsis genome for a homolog of CjMDR1 indicated that a predicted protein of 1286 amino acids, AtPGP4 (At2g47000; hereafter referred to as PGP4), was the most similar Arabidopsis homolog (71% amino acid identity, 68% nucleotide identity).…”
Section: Introductionmentioning
confidence: 99%